Novel Methods for Monitoring and Managing Land and Water Resources in Siberia - Mueller, Lothar; Sheudshen, Askhad K.; Eulenstein, Frank; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book presents an analysis of land and water resources in Siberia, initially characterizing the landscapes, their ecosystems, crucial processes, human impacts on soil and water quality, and the status quo of available research. Further chapters deal with modern monitoring and management methods that can lead to a significant knowledge shift and initiate sustainable soil and water resources use. These include soil hydrological laboratory measurement methods; process-based field evaluation methods for land and water quality; remote sensing and GIS technology-based landscape monitoring methods; process and ecosystem modeling approaches; methods of resource and process evaluation and functional soil mapping; and tools for controlling agricultural land use systems. More than 15 of these concrete monitoring and management tools can immediately be incorporated into research and practice. Maintaining the functions of great landscapes for future generations will be the reward for these efforts.
Land and Water Resources of Siberia, their Functioning and Ecological State -- Status Report about Understanding, Monitoring and Controlling Landscape Processes in Siberia -- Methods for Monitoring the Chemical Composition of Lake Baikal Water -- Microbiological Monitoring of Lake Baikal -- Developing the Regional Indicator Indexes of Zooplankton for Water Quality Class Determination of Water Bodies in Siberia -- Measuring and Estimating Fluxes of Carbon, Major and Trace Elements to the Arctic Ocean -- Measuring Snowmelt in Siberia: Causes, Process and Consequences -- Estimation of Biomass and Net Primary Production (NPP) in West Siberian Boreal Ecosystems: In-Situ and Remote Sensing Methods -- GIS and Remote Sensing Data Based Methods for Monitoring Water and Soil Objects in the Steppe Biome of Western Siberia -- Significant Siberian Vegetation Change is Inevitably Brought on by the Changing Climate.
Keywords: Environment; Hydrology; Climate change; Regional planning; Urban planning; Agriculture; Soil science; Soil conservation; Environment; Soil Science & Conservation; Hydrology/Water Resources; Landscape/Regional and Urban Planning; Agriculture; Environmental Monitoring/Analysis.; Climate Change/Climate Change Impacts; Electronic books